2014
DOI: 10.1002/cncy.21469
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of the cell transfer technique for immunocytochemistry of fine‐needle aspirates

Abstract: BACKGROUND: The use of immunocytochemistry as an important ancillary technique for the workup of fine-needle aspiration (FNA) specimens is an important component in the daily practice of cytopathology. Although cell block preparations are commonly used, immunocytochemistry cannot be completed if the cell blocks are hypocellular. As an alternative approach when conventional cell blocks fail, immunocytochemistry can be performed on cell-transferred direct smears.Multiple immunostains can be applied to a single d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 4 publications
1
24
1
Order By: Relevance
“…[10][11][12][13] In this study, we confirmed its utility to capture sufficient tumor cell DNA for molecular testing if the tissue-embedded paraffin block lacks material. Biopsy samples or fine-needle aspiration cell blocks may only contain a minimal amount of tumor tissue and could be exhausted after the initial routine H&E sections and immunohistochemistry studies.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…[10][11][12][13] In this study, we confirmed its utility to capture sufficient tumor cell DNA for molecular testing if the tissue-embedded paraffin block lacks material. Biopsy samples or fine-needle aspiration cell blocks may only contain a minimal amount of tumor tissue and could be exhausted after the initial routine H&E sections and immunohistochemistry studies.…”
Section: Discussionsupporting
confidence: 55%
“…[10][11][12][13][14][15][16] This technology can also be applied to hematoxylin-eosin (H&E)-stained sections when the cells of interest are exhausted from the paraffin block. In this study we simply set out to establish the CTT as a viable option for isolating tumor cells from H&E-stained slides.…”
mentioning
confidence: 99%
“…However, cell blocks sometimes lack adequate cellularity even when the direct smears are abundantly cellular. The cell transfer technique is a very useful method for obtaining cellular material for immunostaining and molecular testing if conventionally prepared cell blocks lack adequate cellularity [8,[14][15][16][17][18][19]. In our study 15% (24/163) of breast biomarker studies were performed on the cell-transferred smears that otherwise would not have been performed due to inadequate cellularity in the cell block.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ER, PR, and HER2, we can perform GATA3 or mammaglobin ICC on a single cellular smear using the cell transfer technique to confirm the tumor origin from a breast primary. One important limitation to the use of CTT is that only ethanol-fixed direct smears can be used, as air-dried, methanol-fixed slides have previously been shown to have a false negative rate of approximately 30% and also often demonstrate nonspecific background staining [16].…”
Section: Discussionmentioning
confidence: 99%
“…This is useful for cytology specimens, including fine-needle aspirations, in which important or crucial cells may be present on one slide only [17]. In our study, we used touch-preparation specimens of surgically resected NSCLC, and therefore cell blocks were not available.…”
Section: Discussionmentioning
confidence: 99%